Keefektifan model pembelajaran scramble berbantuan media big book terhadap kemampuan membaca permulaan siswa SD Negeri Gondoriyo - Aprillia, Nindya Silvy Wahyu; Purwanti, Kartika Yuni (Trihayu: Jurnal Pendidikan Ke-SD-an, 2024)
This study aims to determine the effectiveness of the scramble learning model aided by the media big book on the reading ability. This type of research is experimental with the form of a nonequivalent control group design. The population in this study was all students of SD Negeri Gondoriyo, and the sample were class IA and IB. Data collection techniques are test and non-test techniques. Test techniques use pretest and posttest while non-test techniques use anchor, observation, and documentation. Data analysis techniques by normality test, homogeneity test, independent sample t-test, simple linear regression test, and paired sample t-test. The results of the study show: (1) There is a difference in SD Negeri Gondoriyo students early reading ability with use of a big book media-aided scramble learning model, with a significance score of 0,002 < 0,05 (2) There is an effect of SD Negeri Gondoriyo students’ initial reading ability with the use of a scramble learning model, with a significance score of 0,011 and 0,000 < 0,05 (3) There is an increased ability to read early SD Negeri Gondoriyo students with the use of a big book media-enabled scramble learning model, with a significance score of 0,000 < 0,05.